ISG20L2 suppresses bortezomib antimyeloma activity by attenuating bortezomib binding to PSMB5 - Yan Yang; Yuhan Gao; Jingcao Huang; Zhuang Yang; Hongmei Luo; Fangfang Wang; Juan Xu; Yushan Cui; Hong Ding; Zhimei Lin; Xinyu Zhai; Ying Qu; et al. (JCI Insight, 2022)
The proteasome inhibitors (PIs) bortezomib and carfilzomib, which target proteasome 20S subunit beta 5 (PSMB5) in cells, are widely used in multiple myeloma (MM) treatment. In this study, we demonstrated the role of interferon-stimulated 20 kDa exonuclease-like 2 (ISG20L2) in MM PI resistance. Gain- and loss-of-function studies showed that ISG20L2 suppressed MM cell sensitivity to PIs in vitro and in vivo. Patients with ISG20L2lo MM had a better response to PIs and a longer overall survival than patients with ISG20L2hi MM. Biotinylated bortezomib pull-down assays showed that ISG20L2 competed with PSMB5 in binding to bortezomib. The surface plasmon resonance assay confirmed the direct binding of bortezomib to ISG20L2. In ISG20L2hi MM cells, ISG20L2 attenuated the binding of bortezomib to PSMB5, resulting in lower inhibition of proteasome activity and therefore less bortezomib-induced cell death. Overall, we identified a potentially novel mechanism by which ISG20L2 conferred bortezomib resistance on MM. The expression of ISG20L2 correlated with MM PI responses and patient treatment outcomes.